Randomised controlled pilot trial of high-velocity, low-amplitude manipulation on cervical and upper thoracic spine levels in asymptomatic subjects (2017)
Background High-velocity, low-amplitude (HVLA) manipulation techniques are habitually used on the cervical spine but the effects are not completely clear. The aim of this prospective comparative trial was to evaluate effects of an indiscriminate manipulation on the C5 (AMC5) a manipulation treatment based on a previous evaluation (MT) and a sham intervention (ST) on cervical spine range of motion (ROM); cervical flexion isometric peak force; EMG activation of sternocleidomastoid muscle (SCM) during the cranio-cervical flexion test (CCFT); and EMG signals of right and left biceps at rest were analyzed. Methods/Design Randomised controlled pilot study and intention-to-treat analysis was performed. Setting The study was conducted at an osteopathic clinic. Methods The outcomes were measured pre and immediately post intervention. Participants A total of 36 asymptomatic subjects (18 male, mean age 30 years) were randomly enrolled into 3 groups: AMC5 (n = 12), MT (n = 12), and ST (n = 12). Results Significant changes (p less than 0.1) were found in the cervical flexion isometric peak force (?13.15%), however, the effect size was considered moderate (d = 0.52). The extension (10.44%) and left rotation ROM (12.25%) showed significant improvement in MT group. During CCFT significant changes were not reported. Conclusions The current pilot study suggested that a tendency toward a decrease in the isometric strength peak in the cervical flexion of the MT group may appear. In cervical ROM the MT group achieved significant effects in extension and left rotation movement. © 2016 Elsevier Ltd